PERAN KEPOLISIAN DALAM MENANGGULANGI PENYALAHGUNAAN NARKOBA DI KOTA PADANG - Teguh Meidaltrio; Eka Vidya Putra (Jurnal Perspektif, 2019)
This study aims to obtain data and know clearly about the Police Policing strategy of the City of Padang in overcoming drug abuse in the City of Padang. This study was analyzed using Action theory by Talcott Parson who compiled a scheme of basic units of social action with the following characteristics, the existence of individuals as actors, actors are seen as hunters for specific goals, actors have alternative means of tools and techniques to achieve goals, actors face with a number of situational conditions that can limit its actions in achieving its goals, the actor is under the constraints of values, norms of various abstract ideas that influence in preventing and overcoming drug abuse to achieve the goal. The method used is a qualitative approach to the type of instrumental case study, and using purposive sampling techniques in the selection of informants. Data collection techniques used were data analysis according to Miles and Huberman which included observations, interviews, and documentation studies. The results of this study show that in preventing drug abuse in Padang Polresta plays an important role in this problem, where one of the objectives of the Padang Polresta is to prevent and overcome drug abuse that occurs in the City of Padang. In preventing drug abuse in the city of Padang, the Padang Police District conducted various activities such as preventive and repressive measures.